2004
DOI: 10.4321/s0365-66912004001200004
|View full text |Cite
|
Sign up to set email alerts
|

Uveítis recurrentes y tratamiento con anticuerpos monoclonales (Daclizumab)

Abstract: Daclizumab is effective and safe for long-term use in the treatment of uveitis which cannot be kept under control by other treatments. In time, it allows the dose of corticosteroids to be decreased or even discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fever, chills, respiratory symptoms and occasionally hypertension are the most common effects. Mucocutaneous reactions and progressive multifocal leukoencephalopathy have been reported [134,135]. The side effects overall are much milder compared with traditional immunosuppressive or chemotherapeutic agents.…”
Section: Adalimumab (Humira)mentioning
confidence: 97%
See 1 more Smart Citation
“…Fever, chills, respiratory symptoms and occasionally hypertension are the most common effects. Mucocutaneous reactions and progressive multifocal leukoencephalopathy have been reported [134,135]. The side effects overall are much milder compared with traditional immunosuppressive or chemotherapeutic agents.…”
Section: Adalimumab (Humira)mentioning
confidence: 97%
“…Reports of success (defined as a reduction of their concomitant immunosuppression load by at least 50% while maintaining their baseline VA at 12 and 26 weeks) with the use of daclizumab in non-infectious intermediate, posterior and panuveitis range from 67 to 80% of the cases. There was concomitant reduction in other immunosuppressants [132][133][134][135]. Papaliodis et al reported favorable results in a case series of daclizumab in the treatment of 14 patients with scleritis, uveitis or mucous membrane pemphigoid unresponsive to other immunosuppressive therapies [136].…”
Section: Adalimumab (Humira)mentioning
confidence: 99%